Nutritional Recommendations for Pregnant Women Receiving Dialysis: A Scoping Review - Elyce Cutajar; Kelly Lambert (Kidney and Dialysis, 2024)
Pregnancy in the dialysing population is an infrequent but increasing event. There is a lack of contemporary guidance regarding the nutritional management of this complex patient group. The aim of this scoping review was to identify, evaluate and summarise the evidence base describing nutritional recommendations for pregnant women receiving dialysis. A systematic search strategy of four databases and the grey literature was conducted. Eligible publications contained reference to recommendations regarding nutrition, supplements, breastfeeding, dietary patterns, and/or weight recommendations for pregnant dialysing women. A total of 136 eligible records were included for synthesis including 66 case reports/case series, 46 reviews, 15 book chapters, 5 editorials, and 4 consensus guidelines/position papers. Recommendations regarding energy, protein, dietary patterns, weight, and vitamin and mineral supplementation were common. However, significant discrepancy across these recommendations was evident. There were limited recommendations regarding other nutrients and breastfeeding. A summary of nutritional recommendations to guide clinical practice was constructed. Pregnancy planning, pre-conception dietetic counselling, interprofessional education, and the guidance synthesised in this review could be utilised by clinicians to improve clinical management and optimise outcomes in these patients. Future research should explore the experiences and perspectives of pregnant dialysing women, investigate nutrient losses during intensive dialysis, and evaluate postpartum follow-up.